Back to Natural Fiber: Wool Color Influences Its Sensitivity to Enzymatic Treatment - Amro A. Amara (The Scientific World Journal)
There are many missed biotechnological opportunities in the developmental countries. Wool quality improvement is one of them. This study is concerning with improving the wool quality using technical enzymes. White wool proves to be more susceptible to the enzymatic treatment than blackish brown wool. This proves that the enzymatic reaction is sensitive to the natural color differences between wool fibers. A simple enzymatic method has been used to improve the wool quality as well as to investigate the changes happened in the wool fibers. Geobacillus stearothermophilus has been used under mesophilic and static cultivation conditions using wool as the main carbon source. These conditions prove to be more suitable for maintaining the fiber structure, less expensive, and reliable as an in-house biotechnological process that can be adapted everywhere. The enzyme activity in case of white wool was 4 Units/ml and for blackish brown wool was 1.5 Units/ml. Electron microscope has been used to evaluate the end result. By following the process included in this paper using probable microbial strain(s), the wool quality improvement can be applied globally and can add another value to the economy of the developmental countries.